Influence of Accounting Policies on Financial Distress: The Moderating Role of Corporate Governance - Fany, Aulia Rezy; Wahidahwati, Wahidahwati; Fidiana, Fidiana (E-Jurnal Akuntansi; Vol 35 No 1 (2025), 2025)
This study investigates the impact of investment policy (IOS), funding policy (LEV), and operational policy (TATO) on financial distress, with good corporate governance (GCG) as a moderating variable. The research employs a quantitative approach, focusing on manufacturing firms listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The sample includes 935 companies, with financial data represented by ratios such as CAPBVA, DAR, TATO, and GCG. Logistic regression analysis is used to evaluate the relationships. The findings reveal that both funding policy and operational policy significantly influence financial distress, whereas investment policy does not exhibit a significant effect. Furthermore, the study shows that GCG moderates the relationship between LEV and financial distress. However, GCG does not moderate the relationships between investment policy or operational policy and financial distress. These results underscore the nuanced role of corporate governance in mitigating financial distress, depending on the specific financial policies under consideration. Keywords: Financial Distress; Investment Policy; Funding Policy; Operating Policy; Good Corporate Governance.